Analytical free energy gradient for the molecular Ornstein-Zernike self-consistent-field method - Yoshida, N. (Condensed Matter Physics, 2007)
An analytical free energy gradient for the molecular Ornstein-Zernike self-consistent-field (MOZ-SCF) method is presented. MOZ-SCF theory is one of the theories to considering the solvent effects on the solute electronic structure in solution. [Yoshida N. et al., J. Chem. Phys., 2000, 113, 4974] Molecular geometries of water, formaldehyde, acetonitrile and acetone in water are optimized by analytical energy gradient formula. The results are compared with those from the polarizable continuum model (PCM), the reference interaction site model (RISM)-SCF and the three dimensional (3D) RISM-SCF.